The European earwig: a model species for studying the (early) evolution of social life - Honorio, R.; Cheutin, M. –C.; Pasquier, L.; de Wever, S.; Perdereau, E.; Villalta, I.; Lécureuil, C.; Meunier, J. (Insectes sociaux, 2025)
When we think of social insects, earwigs rarely come to mind. This is perhaps not surprising, as the term ‘social insect’ has often been used in the literature to refer exclusively to ‘eusocial insects’, i.e. ants, termites and certain bees and wasps. However, earwigs show many aspects of social life. Social interactions in earwigs can occur in groups of up to several hundred individuals, with mothers providing extensive forms of care for their eggs and juveniles, and adults and juveniles showing cooperative behaviour with group members of the same and different ages. In this review, we discuss how research on the European earwig (by far the most studied dermapteran species in terms of its social life) can improve our general understanding of social evolution in insects. After outlining (1) its life cycle and (2) its multiple forms of sociality, we explain how this species advances our knowledge of (3) the interplay between social conflict and cooperation in maintaining facultative social life, (4) the role of pathogens and symbionts in the transition between solitary and social life, (5) the impact of anthropogenic change on social evolution, and (6) the chemical, hormonal and genetic regulation of facultative social behaviour. Overall, this review highlights that the study of social species such as the European earwig can provide unique insights into our general understanding of social evolution and the early evolutionary transitions from solitary to group living.